Fotoinativação de micobactérias de crescimento rápido por porfirinas tetra-catiônicas - Rossi, Grazielle Guidolin (2023)
Antimicrobial Photodynamic Inactivation (aPDI) is an emerging non-invasive treatment that involves the use of a photosensitizer (PS), light and molecular oxygen to inactivate microorganisms. Thus, the application of aPDI has been gaining prominence in the field of microbiology, especially in the treatment of infections that persist after conventional antibiotic therapy. In this scenario are included mycobacterioses, because they do not have many therapeutic options available and they require a slow treatment, thus being promising targets of aPDI. The objective of this work is to explore the action of neutral (4-TPyP and 3- TPyP) and tetra-cationic porphyrins, with peripheral complexes of platinum(II) (3-PtTPyP/4- PtTPyP) and palladium(II) (3-PdTPyP/4-PdTPyP), on Rapidly Growing Mycobacteria (RGM) strains that cause skin and mucous infections. In this study were used standard strains of Mycobacteroides abscessus subsp. abscessus (ATCC 19977), Mycobacteroides abscessus subsp. massiliense (ATCC 48898), Mycolicibacterium fortuitum (ATCC 6841), and Mycolicibacterium smegmatis (ATCC 700084). For this purpose, the susceptibility of microorganisms in the planktonic form was obtained through conventional microdilution techniques and by the time-kill curve. The determination of possible reactive oxygen species (ROS) produced by the PS was carried out using compounds that scavenge these reactive species. The impact of these porphyrins on the mycobacterial surface can be visualized and analyzed through images obtained by the Atomic Force Microscopy (AFM) technique. The results demonstrated the significant antimicrobial activity of the studied porphyrins, with emphasis on the meta substituted isomer 3-PtTPyP and 3-PdTPyP. Furthermore, singlet oxygen (¹O2) was the main reactive species detected, being attributed to it the predominant activity in photo-oxidative damages. Finally, the bactericidal activity of Pt(II) and Pd(II) porphyrins was proven in two irradiation sessions, and the AFM images demonstrate the aggression of these porphyrins on the bacterial cell wall, also their influence on nanomechanical adhesion and electrostatic properties. Therefore, porphyrins are a useful and promising tool to eradicate RGM directly via remote control of light irradiation. The impact and scientific contribution of this work are based on the discovery of a potential new therapeutic approach against cutaneous mycobacterial infections and, in addition, they stimulate the deepening of methodologies that aim at the insertion of porphyrins as a new antimicrobial agent.